1991
DOI: 10.1111/j.1365-2222.1991.tb03203.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of respiratory symptoms to diagnose atopy

Abstract: As reliance of responses to epidemiological questionnaires on atopic symptoms is doubtful, we studied the predictive value of these questions relative to atopy, defined by the presence of serum specific IgE, taking into account some extraneous variables such as age and sex. The study population included 2067 adults, 20-60 years old. The protocol consisted of a standardized questionnaire and an evaluation of serum specific IgE using the Phadiatop (Pharmacia Diagnostics, Uppsala, Sweden) test. The predictive val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 9 publications
3
20
2
Order By: Relevance
“…In contrast to our findings, Vervloet et al (12) found a decrease of the percentage with positive Phadiatop tests with age much more sharply in men than in women.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In contrast to our findings, Vervloet et al (12) found a decrease of the percentage with positive Phadiatop tests with age much more sharply in men than in women.…”
Section: Discussioncontrasting
confidence: 56%
“…In a recent study, Omenaas et al (5) found higher prevalences of specific IgE to house-dust mite and cat in men than in women in the Norwegian adult general population, but no sex differences for timothy grass, birch, and Cludosporium. In the French population aged 20-60 years, Vervloet et al (12) found a higher percentage of positive Phadiatop tests in men (22%) than in women (17%). Whether these results agree with our results depends on the nature of the aeroallergens used in the mixture of the Phadiatop test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that there is no clear relationship between allergic sensitization and allergic symptoms. 17,[51][52][53] Although allergic sensitization often overlaps with the occurrence of allergic symptoms, there are also many children without allergen-specific serum IgE/positive SPT that do develop allergic symptoms 17,19,21,22,26,31 and vice versa. 43 There might be a different …”
Section: Discussionmentioning
confidence: 99%
“…Objective tests for the diagnosis of IgE-mediated allergy (skin prick tests, allergen-specific serum IgE) can be used (29)(30)(31). In both developed and developing countries, a large percentage of patients with an epidemiologic definition of Ôallergic rhinitisÕ do not have positive skin tests or serum-specific IgE (5-9, 32, 33).…”
Section: Epidemiologic Studiesmentioning
confidence: 99%